Evidence for syntactic audience design from the production of active and passive relative clauses in Chinese - Tao, Lan; Gerwien, Johannes (Lingua, 2025)
This study examines audience design at the syntactic level. We report two language production experiments investigating how Mandarin Chinese speakers choose between object relative clauses (ORCs) and passive subject relative clauses (pSRCs) to refer to patients in target events. These structures differ in syntactic function assignments. The production experiments vary in whether or not speakers interact with a real listener (Experiment 1 and 2). Two factors were manipulated: (1) the number of events in the visual stimuli eliciting verbal responses, and (2) the animacy configuration of referents. Results show that speakers adjust their syntactic choices to facilitate comprehension, with effects varying by the presence of a listener. Syntactic adaptations also increase production difficulty to some extent. A third experiment complements the findings with a language comprehension study using the visual world paradigm. The target responses from Experiments 1 and 2 served as the linguistic structures from which auditory stimuli were produced. Results reveal that the structure speakers avoided to produce under certain conditions (pSRCs with two depicted events) hindered comprehension, whereas the same structure improved comprehension in simpler contexts (pSRCs with one event). We discuss the findings with reference to different language production models.